Pengaruh Pengungkapan Corporate Social Responsibility dan Return on Asset terhadap Nilai Perusahaan Manufaktur yang Terdaftar di Jakarta Islamic Index (JII) Tahun 2018-2022 - Oktaviani, Siti Atikah; Tripalupi, Ramadhani Irma; Wardiyah, Mia Lasmi (CV. Kalimasada Group, 2023)
The purpose of this research is to find out and analyze the CSR disclosure reporting mechanism; the influence of CSR disclosure on Company Value; the effect of disclosure of ROA on Company Value; and the joint effect of CSR and ROA on Company Value (in Manufacturing Companies registered on JII for 2018-2022. The research method used in this research is Mixed Methods. This research uses the Mixed Methods method with the type of approach in the form of